Preclinical Evaluation of CD64 As a Potential Target For CAR-T-cell Therapy For Acute Myeloid Leukemia. Issue 2 (6th February 2022) - Sun, Xiaolei; Wang, Guoling; Zuo, Shiyu; Niu, Qing; Chen, Xiaoli; Feng, Xiaoming
Abstract : Supplemental Digital Content is available in the text. Abstract : The relapsed and refractory acute myeloid leukemia (AML) patients receiving traditional chemotherapies have poor survival rate. Chimeric antigen receptor (CAR)-modified T cells have demonstrated remarkable effectiveness against some malignancies. However, most of CAR-Ts targeting the candidate proteins on AML cells induce hematopoietic cell suppression. Because of extensive heterogeneity among different types of AML, it is essential to expand the choice of target antigen for the CAR-T treatment of AML. CD64 ( FcγRI ) is a transmembrane protein with broad expression on various types of AML cells, especially monocytic AML cells, but it is absent on hematopoietic stem cells (HSCs) and most of nonmonocytes. Here, we found that some types of AML patients showed the homogeneous high-level expression of CD64. So, we created a CAR-T targeting CD64 (64bbz) and further verified its high efficiency for eradicating CD64 + AML cells. In addition, 64bbz showed no cytotoxicity to HSCs. Overall, we developed a new treatment option for AML by using CD64 CAR-T cells while avoiding ablation of HSCs.